Biological screening of herbal extracts and essential oil from Plectranthus species: α-amylase and 5-lipoxygenase inhibition and antioxidant and anti-Candida potentials - Simony Carvalho Mendonça; Smail Aazza; Alexandre Alves de Carvalho; Diogo Mendes da Silva; Nelma de Mello Silva Oliveira; José Eduardo Brasil Pinto Pinto; Suzan Kelly Vilela Bertolucci (Universidade de São Paulo, 2023)
Abstract The phenolic compound content, the antioxidant and α-amylase inhibition potentials of different extracts of the Plectranthus amboinicus, P. barbatus and P. ornatus were evaluated. We also evaluated the influence of plant growth and harvest time on the chemical composition of the essential oil (EO) of P. amboinicus, its antioxidant and anti-Candida activities and the α-amylase and lipoxygenase inhibitions. The turbo-extract of P. barbatus showed the greatest phenolic compound content and antioxidant activity. No α-amylase inhibition activity was observed in the analyzed extracts, but the turbo-extraction and refluxing extracts possessed high antioxidant activities. Protected cultivation and morning harvest conditions gave the best antioxidant activities, which was associated to the highest carvacrol content. P. amboinicus EO antioxidant activity could contribute to the reduction of oxidative stress in diabetes. Causal Candida strains of diabetic foot ulcers showed sensitivity to P. amboinicus EO. C. albicans and C. dubliniensis were the most sensitive of the selected Candida strains. Turbo-extracts or refluxing of the three species extracts and the EO of P. amboinicus should be considered as a potential candidate for the management the complications of type 2 diabetes.